Penguatan Literasi Hukum dan Peran Woman Crisis Center bagi Siswa Sekolah Perempuan di Kabupaten Nganjuk - Ratna Frenty Nurkhalim; Dianti Ias Oktaviasari; Endah Retnani Wismaningsih; Vivien Dwi Purnamasari; Indah Susilowati; Pinda Duana Wahyu Purwantaris; Almira Maudy Sukmaning Putri; Amanda Putri Aprilya; Ferina Devitasari (GUYUB: Journal of Community Engagement, 2025)
Four out of five victims of violence in Indonesia are women, highlighting a serious issue that significantly impacts societal well-being. To address this problem, Nganjuk Regency has initiated a gender equality program called SAPA MAMA. SAPA MAMA students, as role models and agents of change for women's empowerment, must understand the dangers of violence against women and the appropriate actions to take when encountering such incidents. This community engagement program aims to enhance SAPA MAMA students' knowledge regarding the main tasks and functions of the Women's Crisis Center (WCC) as a service institution for victims of violence against women and children. By implementing a situation-based learning approach, 48 participants from various age groups took part in an educational program covering topics such as the role of WCC, types of violence, and complaint regulations. A pre-test and post-test were conducted to assess participants' comprehension before and after the intervention. Statistical analysis revealed a significant improvement in knowledge scores, with an average increase of 28.8% after the educational session. Furthermore, the Wilcoxon Signed Rank test yielded a p-value of < 0.05, indicating that the educational program was effective in enhancing participants' understanding. These findings emphasize the importance of collaboration between local governments, community organizations, and WCCs in raising awareness about violence. It is recommended that this program be expanded to other villages to maximize its impact on the broader community.